Social stratification and allostatic load: shapes of health differences in the MIDUS study in the United States. Issue 5 (28th January 2019) - Rodriguez, Javier M.; Karlamangla, Arun S.; Gruenewald, Tara L.; Miller-Martinez, Dana; Merkin, Sharon S.; Seeman, Teresa E.
Abstract: Social stratification is an important mechanism of human organization that helps to explain health differences between demographic groups commonly associated with socioeconomic gradients. Individuals, or group of individuals, with similar health profiles may have had different stratification experiences. This is particularly true as social stratification is a significant non-measurable source of systematic unobservable differences in both SES indicators and health statuses of disadvantage. The goal of the present study was to expand the bulk of research that has traditionally treated socioeconomic and demographic characteristics as independent, additive influences on health by examining data from the United States. It is hypothesized that variation in an index of multi-system physiological dysregulation – allostatic load – is associated with social differentiation factors, sorting individuals with similar demographic and socioeconomic characteristics into mutually exclusive econo-demographic classes. The data were from the Longitudinal and Biomarker samples of the national Study of Midlife Development in the US (MIDUS) conducted in 1995 and 2004/2006. Latent class analyses and regression analyses revealed that physiological dysregulation linked to socioeconomic variation among black people, females and older adults are associated with forces of stratification that confound socioeconomic and demographic indicators. In the United States, racial stratification of health is intrinsically related to the degree to which black people in general, and black females in particular, as a group, share an isolated status in society. Findings present evidence that disparities in health emerge from group-differentiation processes to the degree that individuals are distinctly exposed to the ecological, political, social, economic and historical contexts in which social stratification is ingrained. Given that health policies and programmes emanate from said legal and political environments, interventions should target the structural conditions that expose different subgroups to different stress risks in the first place.